Virulence Factors in Hypervirulent Klebsiella pneumoniae - Zhu, Jie; Wang, Tao; Chen, Liang; Du, Hong (Frontiers in Microbiology, 2021)
Hypervirulent Klebsiella pneumoniae (hvKP) has spread globally since first described in the Asian Pacific Rim. It is an invasive variant that differs from the classical K. pneumoniae (cKP), with hypermucoviscosity and hypervirulence, causing community-acquired infections, including pyogenic liver abscess, pneumonia, meningitis, and endophthalmitis. It utilizes a battery of virulence factors for the survival and pathogenesis, such as capsule, siderophore, lipopolysaccharide, fimbriae, outer membrane proteins, and type 6 secretion system, of which the former two are dominant. This review summarizes these hvKP-associated virulence factors in order to understand its molecular pathogenesis and shed light on new strategies to improve the prevention, diagnosis, and treatment of hvKP-causing infection.